Analysing the Spatial and Temporal Characteristics of Ecological Land Encroachment by Cropland Expansion and Its Drivers in Cambodia - Danni Su; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Lusha Ma; Jingcong Ma; Tao Li (Land)
The rapid expansion of cropland in Cambodia, the world’s seventh-largest rice exporter, has created an imbalance in land use structure. However, there is a lack of quantitative investigation of the loss of ecological land as a result of the expansion of cropland and its drivers. In this research, spatial autocorrelation, landscape pattern index and transfer matrix methods were used based on land use data from 2000 to 2023. Then, the eXtreme Gradient Boosting-SHapley Additive exPlanations (XGBoost-SHAP) and Geographic Detector were used to explore the drivers of cropland expansion. The findings indicate that the expanse of agricultural land in Cambodia has significantly increased by 13.47%. The proportion of cropland to the land area (37.87%) is close to that of forest (40.19%). Cultivated land is dominated by rice fields, supplemented by drylands. Spatial clustering is obvious in both drylands and rice fields. Drylands are mainly concentrated in the eastern and western mountainous areas and the northern border, while rice fields are concentrated in the central plains. Cultivated land encroached on a total of 30,579.27km2 of ecological land, of which 62.88% was dry land and 37.12% was rice fields. Forests and shrubs are the main source of expansion of cropland. In addition, soil type (0.18), elevation (0.17) and GDP (0.17), population (0.52) and their interactions strongly drove the expansion of dryland and rice fields. Cambodia should conduct scientific research to assess the demand for cropland by population growth and economic progress. It should realize the orderly growth of cultivated land, reduce the damage to ecological land, and promote the coordinated development of society, environment and economy.